Developing oneself to serve others? Servant leadership practices of mindfulness-trained leaders - Urrila, Laura; Eva, Nathan (Elsevier, 2024)
To advance the research on servant leadership development, we explore if and how mindfulness training may help develop servant leadership behaviors. We present findings of a pre-intervention inquiry and post-intervention interviews with 62 leaders who participated in an eight-week-long mindfulness intervention. We detect three mechanisms that explicate how mindfulness-trained leaders engage in servant leadership to benefit themselves, their followers, and the work community: 1) Developing oneself as a servant leader (self-awareness and self-care), 2) Serving the follower (relationship building, follower development and follower well-being), and 3) Serving the team (team culture). In doing so, this study strengthens the theoretical bridge between leader mindfulness and servant leadership by demonstrating how these literatures can build upon each other and how mindfulness interventions can be used to develop servant leaders from both a leader development (intra-individual) and a leadership development (inter-individual) lens.
Keywords: Leader development; Leadership development; Mindfulness intervention; Servant leadership; Qualitative; mindfulness; fi=Henkilöstöjohtaminen|en=Human Resource Management|